Three-dimensional graphene foam supported Fe3O4 lithium battery anodes with long cycle life and high rate capability - Luo, Jingshan (2013)
Fe3O4 has long been regarded as a promising anode material for lithium ion battery due to its high theoretical capacity, earth abundance, low cost and nontoxic properties. However, up to now, no effective and scalable method has been realized to overcome the bottleneck of poor cyclability and low rate capability. In this article, we report a bottom up strategy assisted by atomic layer deposition (ALD) to graft bicontinuous mesoporous nanostructure Fe3O4 onto three dimensional (3D) graphene foams and directly use the composite as the lithium ion battery anode. This electrode exhibits high reversible capacity and fast charging and discharging capability. A high capacity of 785 mAh/g is achieved at 1C rate and is maintained without decay up to 500 cycles. Moreover, the rate of up to 60C is also demonstrated, rendering a fast discharge potential. To our knowledge, this is the best reported rate performance for Fe3O4 in lithium ion battery to date.